2010
DOI: 10.1289/ehp.0901200
|View full text |Cite
|
Sign up to set email alerts
|

Barrier Capacity of Human Placenta for Nanosized Materials

Abstract: BackgroundHumans have been exposed to fine and ultrafine particles throughout their history. Since the Industrial Revolution, sources, doses, and types of nanoparticles have changed dramatically. In the last decade, the rapidly developing field of nanotechnology has led to an increase of engineered nanoparticles with novel physical and chemical properties. Regardless of whether this exposure is unintended or not, a careful assessment of possible adverse effects is needed. A large number of projects have been c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
363
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 525 publications
(380 citation statements)
references
References 29 publications
9
363
0
8
Order By: Relevance
“…Further representative results obtained with the ex vivo dual recirculating human placental perfusion model were published recently 11,19 . 19 .…”
Section: Representative Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Further representative results obtained with the ex vivo dual recirculating human placental perfusion model were published recently 11,19 . 19 .…”
Section: Representative Resultsmentioning
confidence: 99%
“…Click here to view larger figure. 19 . The ratios between fetal and maternal concentrations of 14 C-antipyrine and polystyrene particles were calculated after 180 min of placenta perfusion.…”
Section: Representative Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our experiments have also confirmed that at concentrations up to 200 μg/ml, PEGylated PLGA nanoparticles are not cytotoxic to trophoblast cells, and are therefore an ideal drug delivery platform. It has previously been shown that polymeric particles approximately 100 nm in diameter can cross the placenta [12,35]. In this work, digoxin-loaded nanoparticles were synthesized by a modified solvent displacement method, which resulted in high encapsulation efficiency, narrow polydispersity and appropriate p article size to promote transplacental drug delivery.…”
Section: Discussionmentioning
confidence: 99%